Cryptotanshinone Inhibits ERα-Dependent and -Independent BCRP Oligomer Formation to Reverse Multidrug Resistance in Breast Cancer - Ni, Wenting; Fan, Hui; Zheng, Xiuqin; Xu, Fangming; Wu, Yuanyuan; Li, Xiaoman; Wang, Aiyun; Huang, Shile; Chen, Wenxing; Wang, Shijun; Lu, Yin (Frontiers in Oncology, 2021)
Both long-term anti-estrogen therapy and estrogen receptor-negative breast cancer contribute to drug resistance, causing poor prognosis in breast cancer patients. Breast cancer resistance protein (BCRP) plays an important role in multidrug resistance. Here we show that cryptotanshinone (CPT), an anti-estrogen compound, inhibited the oligomer formation of BCRP on the cell membrane, thus blocking its efflux function. The inhibitory effect of CPT on BCRP was dependent on the expression level of estrogen receptor α (ERα) in ERα-positive breast cancer cells. Furthermore, ERα-negative breast cancer cells with high expression of BCRP were also sensitive to CPT, because CPT was able to bind to BCRP and inhibit its oligomer formation on the cell membrane, suggesting that the high level of BCRP expression is crucial for CPT to reverse drug resistance. The combination of CPT and chemotherapeutic agents displayed enhanced anticancer effects. The results suggest that CPT is a novel BCRP inhibitor via blocking the oligomer formation of BCRP on the cell membrane. CPT is able to inhibit the activity of BCRP in an ERα-dependent and -independent manner, sensitizing breast cancer cells to chemotherapy.